The Foot and Ankle Kinematics of a Simulated Progressive Collapsing Foot Deformity During Stance Phase: A Cadaveric Study. (December 2022) - Henry, Jensen K.; Hoffman, Jeffrey; Kim, Jaeyoung; Steineman, Brett; Sturnick, Daniel; Demetracopoulos, Constantine; Deland, Jonathan; Ellis, Scott
Background: Progressive collapsing foot deformity (PCFD) is a complex pathology associated with tendon insufficiency, ligamentous failure, joint malalignment, and aberrant plantar force distribution. Existing knowledge of PCFD consists of static measurements, which provide information about structure but little about foot and ankle kinematics during gait. A model of PCFD was simulated in cadavers (sPCFD) to quantify the difference in joint kinematics and plantar pressure between the intact and sPCFD conditions during simulated stance phase of gait. Methods: In 12 cadaveric foot and ankle specimens, the sPCFD condition was created via sectioning of the spring ligament and the medial talonavicular joint capsule followed by cyclic axial compression. Specimens were then analyzed in intact and sPCFD conditions via a robotic gait simulator, using actuators to control the extrinsic tendons and a rotating force plate underneath the specimen to mimic the stance phase of walking. Force plate position and muscle forces were optimized using a fuzzy logic iterative process to converge and simulate in vivo ground reaction forces. An 8-camera motion capture system recorded the positions of markers fixed to bones, which were then used to calculate joint kinematics, and a plantar pressure mat collected pressure distribution data. Joint kinematics and plantar pressures were compared between intact and sPCFD conditions. Results: The sPCFD condition increased subtalar eversion in early, mid-, and late stance ( P < .05), increased talonavicular abduction in mid- and late stance ( P < .05), and increased ankle plantarflexion ( P < .05), adduction ( P < .05), and inversion ( P < .05). The center of plantar pressure was significantly ( P < .01) medialized in this model of sPCFD and simulated stance phase of gait. Discussion: Subtalar and talonavicular joint kinematics and plantar pressure distribution significantly changed with the sPCFD and in the directions expected from a PCFD foot. We also found that ankle joint kinematics changed with medial and plantar drift of the talar head, indicating abnormal talar rotation. Although comparison to an in vivo PCFD foot was not performed, this sPCFD model produced changes in foot kinematics and indicates that concomitant abnormal changes may occur at the ankle joint with PCFD. Clinical Relevance: This study describes the dynamic kinematic and plantar pressure changes in a cadaveric model of simulated progressive collapsing foot deformity during simulated stance phase.